2010
DOI: 10.1515/jpem.2010.182
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial Effusion in Severe Hypothyroidism in Children

Abstract: Pleural and pericardial effusion is a rare complication of severe hypothyroidism in children but can be present in 10 to 30 % of adults. Most pediatric cases have been in children with Down syndrome. In this report, six cases of pericardial effusion in children with severe hypothyroidism with and without trisomy 21 are presented. In all patients, the pericardial effusion was managed successfully without pericardiocentesis. The effusions resolved completely in 2 to 12 months after initiation of thyroxin replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 9 publications
1
24
0
1
Order By: Relevance
“…Echocardiographic studies on children have shown that individuals with Down syndrome have a significantly higher prevalence of isolated pericardial effusions compared to controls [Concolino et al, 2005]. So far the association of pericardial effusion and hypothyroidism has repeatedly been reported in children [Martinez-Soto et al, 2010;Anah et al, 2011] but as yet only in two cases of male adults with Down syndrome [Said et al, 2007;Toorians and van Ekelen, 2007]. So far the association of pericardial effusion and hypothyroidism has repeatedly been reported in children [Martinez-Soto et al, 2010;Anah et al, 2011] but as yet only in two cases of male adults with Down syndrome [Said et al, 2007;Toorians and van Ekelen, 2007].…”
Section: To the Editormentioning
confidence: 99%
See 3 more Smart Citations
“…Echocardiographic studies on children have shown that individuals with Down syndrome have a significantly higher prevalence of isolated pericardial effusions compared to controls [Concolino et al, 2005]. So far the association of pericardial effusion and hypothyroidism has repeatedly been reported in children [Martinez-Soto et al, 2010;Anah et al, 2011] but as yet only in two cases of male adults with Down syndrome [Said et al, 2007;Toorians and van Ekelen, 2007]. So far the association of pericardial effusion and hypothyroidism has repeatedly been reported in children [Martinez-Soto et al, 2010;Anah et al, 2011] but as yet only in two cases of male adults with Down syndrome [Said et al, 2007;Toorians and van Ekelen, 2007].…”
Section: To the Editormentioning
confidence: 99%
“…However, it is still unclear whether the high prevalence of pericardial effusions in patients with Down syndrome is caused by hypothyroidism or if it should be considered an isolated finding. Pericardial effusions associated with hypothyroidism resolved after treatment with levothyroxine [Said et al, 2007;Toorians and van Ekelen, 2007;Martinez-Soto et al, 2010]. Pericardial effusions associated with hypothyroidism resolved after treatment with levothyroxine [Said et al, 2007;Toorians and van Ekelen, 2007;Martinez-Soto et al, 2010].…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…While pleural or pericardial effusions are noted in 10% to 30% of the adult hypothyroidism patients, this complication is rare in children (Martinez-Soto et al, 2010). The main symptoms of cardiac tamponade in hypothyroid patients are increased or normal heart rate (after pericardiocentesis, the tempo is slowed) distant heart sounds, enlarged jugular veins, low P valves, T valves and QRS complex in the electrocardiogram and massive pericardial effusion in echocardiography.…”
Section: Connective Tissue In the Heartmentioning
confidence: 99%